Modern spectroscopy - Hollas, J. Michael (J. Wiley, 2010)
The latest edition of this highly acclaimed title introduces the reader to a wide range of spectroscopies, and includes both the background theory and applications to structure determination and chemical analysis. It covers rotational, vibrational, electronic, photoelectron and Auger spectroscopy, as well as EXAFs and the theory of lasers and laser spectroscopy. * A revised and updated edition of a successful, clearly written book * Includes the latest developments in modern laser techniques, such as cavity ring-down spectroscopy and femtosecond lasers * Provides numerous worked examples, calculations and questions at the end of chapters